“THE INFLUENCE OF PROMOTIONS AND PRODUCT PRICING ON PURCHASING DECISIONS FOR EMINA PRODUCTS IN BIREUEN REGENCY” - Ovi Satria; Niswatul Khaira; Khaira Maulida; Nia Maulina; Sri Yanna (Universitas Efarina, 2024)
This study investigates the impact of promotional strategies and pricing on consumer purchasing decisions for Emina products in Bireuen Regency. The research aims to identify how these factors influence consumer behavior and their decision-making process regarding beauty and skincare products.